Y chromosome microdeletions in Chinese men with infertility: prevalence, phenotypes, and intracytoplasmic sperm injection outcomes - Dongjia Chen; Guoqing Fan; Xianqing Zhu; Qinyun Chen; Xuren Chen; Feng Gao; Zexin Guo; Peng Luo; Yong Gao (BMC, 2023)
Abstract Background The incidence of Y chromosome microdeletions varies among men with infertility across regions and ethnicities worldwide. However, comprehensive epidemiological studies on Y chromosome microdeletions in Chinese men with infertility are lacking. We aimed to investigate Y chromosome microdeletions prevalence among Chinese men with infertility and its correlation with intracytoplasmic sperm injection (ICSI) outcomes. Methods This single-center retrospective study included 4,714 men with infertility who were evaluated at the Reproductive Center of the First Affiliated Hospital of Sun Yat-sen University between May 2017 and January 2021. Semen analysis and Y-chromosome microdeletion via multiplex polymerase chain reaction were conducted on the men. The study compared outcomes of 36 ICSI cycles from couples with male azoospermia factor (AZF)cd deletions with those of a control group, which included 72 ICSI cycles from couples without male Y chromosome microdeletions, during the same period. Both groups underwent ICSI treatment using ejaculated sperm. Results Among 4,714 Chinese men with infertility, 3.31% had Y chromosome microdeletions. The combined deletion of sY254 and sY255 in the AZFc region and sY152 in the AZFd region was the prevalent pattern of Y chromosome microdeletion, with 3.05% detection rate. The detection rates of AZF deletions in patients with normal total sperm count, mild oligozoospermia, severe oligozoospermia, cryptozoospermia, and azoospermia were 0.17%, 1.13%, 5.53%, 71.43%, and 7.54%, respectively. Compared with the control group, the AZFcd deletion group exhibited no significant difference in the laboratory results or pregnancy outcomes of ICSI cycles using ejaculated sperm. Conclusions This is the largest epidemiological study on Y chromosome microdeletions in Chinese men with infertility. The study results underline the necessity for detecting Y chromosome microdeletion in men with infertility and severe sperm count abnormalities, especially those with cryptozoospermia. The combined deletion of sY254 and sY255 in the AZFc region and sY152 in the AZFd region was the most prevalent Y chromosome microdeletion pattern. Among patients with AZFcd deletion and ejaculated sperm, ICSI treatment can result in pregnancy outcomes, similar to those without AZFcd deletion.